Assessment of genetic variations of silver lime (Tilia tomentosa Moench.) by RAPD markers in urban and forest ecosystems - ÖZYİĞİT, İBRAHİM İLKER (TAYLOR & FRANCIS LTD, 2015)
In the present study, the genetic diversity analysis of Tilia tomentosa plants was performed by using random amplified polymorphic DNA (RAPD) primers. Twenty eight plant samples, collected from urban (25 members) and forest (3 members) ecosystems, were used in this study. A total of 53 bands were obtained from eight RAPD primers, of which 48 (90.6%) were polymorphic. The percentage of polymorphic loci (P) was found to be 94.29%, the observed number of alleles (Na) was 1.94, the effective number of alleles (Ne) was 1.60, Nei's gene diversity (h) was 0.34 and Shannon's information index (I) was 0.50. Unweighted pair group method with arithmetic mean (UPGMA) cluster analysis revealed two major groups. Members of the urban and forest ecosystems showed high genetic similarity (28%-92%) and they did not separate from each other in UPGMA tree. Furthermore, urban and forest genotypes clustered together in principal component analysis.
Keywords: genetic diversity; principal component analysis (PCA); UPGMA; urban ecosystem; AMPLIFIED POLYMORPHIC DNA; ECOLOGICAL CHARACTERISTICS; POPULATION-GENETICS; DIVERSITY; ISTANBUL; DISTRICT; NORTH; CHINA; FLORA